SHOULD EXCESSIVE MARKETING EXPENSES BE REMUNERATED? LESSONS FROM INDONESIA’S TAX COURT DECISIONS - Dwindahany, Cut Sarah; Efendi, Subagio (Fakultas Syariah, 2024)
This study examines the causes of remuneration disputes over excessive marketing expenditures that enhance marketing intangibles value and suggests solutions for fairly remunerating such excessive marketing activities. Based on existing literature, this study investigates the causes of disputes using four factors that affect the effectiveness of transfer pricing audits. This study employs a qualitative method using case studies of Indonesia’s tax court decisions from 2020 to 2023. The primary and secondary data are collected through interviews and existing data support and validated further using triangulations. Findings reveal that the disputes are mainly caused by weak proof of the correction made by the tax authority. Applying the arm's length principle became highly subjective due to the unclear transfer pricing regulations, inadequate assessment of the company's business complexity, and lack of comparable data. The tax authority should improve domestic regulations on transfer pricing and disclose taxpayers' nominative list of promotional expenses to implement appropriate corrections in this case. Empirically, this study has novelty by using the perspective of tax court’s judges and is based on tax court decisions in Indonesia. Practically, this research is useful in examining the amount of arm’s length remuneration for excessive marketing activities. Penelitian ini meneliti penyebab dari sengketa remunerasi atas biaya pemasaran yang berlebihan yang dianggap meningkatkan nilai aset pemasaran tak berwujud dan menyarankan solusi untuk memberikan remunerasi yang adil atas aktivitas pemasaran yang berlebihan tersebut. Berdasarkan literatur yang ada, penelitian ini menyelidiki penyebab perselisihan dengan menggunakan empat faktor yang mempengaruhi efektivitas audit transfer pricing. Penelitian ini menggunakan metode kualitatif dengan menggunakan studi kasus putusan pengadilan pajak Indonesia dari tahun 2020 hingga 2023. Data primer dan sekunder dikumpulkan melalui wawancara dan data pendukung yang ada, dan divalidasi lebih lanjut dengan menggunakan triangulasi. Hasil penelitian mengungkapkan bahwa sengketa terutama disebabkan oleh lemahnya pembuktian atas koreksi yang dilakukan oleh otoritas pajak. Penerapan prinsip kewajaran dan kelaziman usaha menjadi sangat subyektif karena peraturan penetapan harga transfer yang tidak jelas, penilaian yang kurang memadai atas kompleksitas bisnis perusahaan, dan kurangnya data pembanding. Otoritas pajak harus memperbaiki peraturan domestik tentang transfer pricing dan mengungkapkan daftar nominatif biaya promosi wajib pajak untuk menerapkan koreksi yang tepat dalam kasus ini. Secara empiris, penelitian ini memiliki kebaruan dengan menggunakan perspektif hakim pengadilan pajak dan didasarkan pada putusan pengadilan pajak di Indonesia. Secara praktis, penelitian ini bermanfaat dalam mengkaji besaran remunerasi yang wajar atas kegiatan pemasaran yang berlebihan.